Optimization of operational plans based on BWM-QFD method - YIN Xing, PENG Shaohui, FANG Bing (Zhihui kongzhi yu fangzhen, 2025)
The optimization of operational plans is the key phase of operational planning, and the decision quality is directly related to the success or failure of the war. Aiming at the optimization question of operational plans, this paper proposes optimization of operational plans based on BWM-QFD method. Firstly, this method builds the house of quality on optimization of operational plans, and establishes the connection of plan satisfaction requirement and capability index. Secondly, this method uses BWM to calculate the weight of plan satisfaction requirement, builds the optimization framework of operational plans, and proposes the evaluation algorithm of plan satisfaction requirement. At last, through the case of optimization of operational plans, the effectiveness and the implementability of this method is numerically verified.